Peer Observation and Evaluation Tool (POET): A Formative Peer Review Supporting Scholarly Teaching - Jeffrey L. Crabtree; Patricia J. Scot; Fengyi Kuo (Scholarworks @ WMU, 2016)
The Peer Observation and Evaluation Tool (POET) is a valid and reliable measure developed for formative peer evaluation of pharmacy faculty. The authors replicated a study conducted on the POET in pharmacy in order to report the instrument's validity and reliability in occupational therapy and to explore its potential as a formative teaching evaluation for occupational therapy educators. To verify item importance, seven participants from the faculty in an occupational therapy department rated each item. To establish inter-rater reliability, the participants evaluated one videotaped 55 min lecture. The POET was reliable with ICC at 0.93. There were high levels of agreement with the importance ratings among the participants with all scales. The POET appears to be a valid and reliable formative measure of teaching. At a time of significant change in the level of occupational therapy education, this measure may be an important support for scholarly teaching in two ways: First, this measure offers several opportunities to document the instructor's strengths and, second, it offers the instructor suggestions about ways to improve teaching quality. Finally, the POET may facilitate faculty professional growth and development through systematic, strategic, and constructive peer review feedback.